1995
DOI: 10.1042/bj3090853
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of the lipoate protein ligase of Escherichia coli

Abstract: Lipoate is an essential component of the 2-oxoacid dehydrogenase complexes and the glycine-cleavage system of Escherichia coli. It is attached to specific lysine residues in the lipoyl domains of the E2p (lipoate acetyltransferase) subunit of the pyruvate dehydrogenase complex by a Mg(2+)- and ATP-dependent lipoate protein ligase (LPL). LPL was purified from wild-type E. coli, where its abundance is extremely low (< 10 molecules per cell) and from a genetically amplified source. The purified enzyme is a monome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
118
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 46 publications
2
118
1
Order By: Relevance
“…S4B), for cocrystallization. Sulfamoyladenosine analogs have been used to generate competitive inhibitors of aminoacyl-tRNA synthetases (23), and biotin sulfamoyladenosine is a competitive inhibitor of E. coli biotin ligase (24), an enzyme structurally and functionally homologous to LplA (25,26). We confirmed that resorufin ligase was able to bind resorufin sulfamoyladenosine and proceeded to crystallize the ligase in the presence of this analog.…”
Section: Structure-based Mutagenesis and Screening For Resorufin Ligasementioning
confidence: 55%
“…S4B), for cocrystallization. Sulfamoyladenosine analogs have been used to generate competitive inhibitors of aminoacyl-tRNA synthetases (23), and biotin sulfamoyladenosine is a competitive inhibitor of E. coli biotin ligase (24), an enzyme structurally and functionally homologous to LplA (25,26). We confirmed that resorufin ligase was able to bind resorufin sulfamoyladenosine and proceeded to crystallize the ligase in the presence of this analog.…”
Section: Structure-based Mutagenesis and Screening For Resorufin Ligasementioning
confidence: 55%
“…LplA activates and transfers not only naturally occurring R-(ϩ)-lipoate but also S-(Ϫ)-lipoate, lipoate analogues, and octanoate to the apoproteins, although S-lipoate and octanoate are used at a 44 and 16% rate of R-lipoate, respectively (5,6). LplA has a molecular mass of 37,795 Da, consisting of 337 amino acids excluding the initiating methionine residue, which is cleaved off during the biosynthesis (5).…”
Section: Reactionmentioning
confidence: 99%
“…In E. coli, lipoyl groups can be incorporated by at least two routes (Figure 1). Scavenged lipoic acid can be utilized by ATP dependent activation and attachment via an amide bond to the lysine residue of the LCD in a reaction catalyzed by the LplA [2]. Alternatively, de novo lipoyl cofactor biosynthesis proceeds initially by octanoylation of the LCD lysine residue [3].…”
Section: Introductionmentioning
confidence: 99%